Pengaruh Leader Humility Terhadap Withdrawal Behavior di Moderasi oleh Interpersonal Justice - Hairul Arifqi; Ali Jufri; Risdianto (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
This study aims to analyze the influence of Leader Humility on Withdrawal Behavior with Interpersonal Justice as a moderating variable at PT. Saung Bukit Ajimut, a fast food restaurant in Cirebon Regency. The research approach used was quantitative with a survey method. Data were collected through questionnaires distributed to employees, then analyzed using Moderated Regression Analysis (MRA) with the help of SPSS. The results showed that Leader Humility had a negative and significant effect on Withdrawal Behavior. The higher the leader's humility, the lower the tendency of employees to display withdrawal behavior such as lateness, absenteeism, and decreased work motivation. However, the Interpersonal Justice variable was not proven to be able to moderate the relationship between Leader Humility and Withdrawal Behavior. This indicates that the perception of interpersonal justice is not strong enough to strengthen the influence of leader humility because the restaurant's work dynamics are more influenced by structural factors such as workload and reward systems. This study recommends companies to strengthen the consistency of humble leadership practices, manage workloads fairly, improve two-way communication forums, and integrate interpersonal justice with reward systems so that employee withdrawal behavior can be suppressed sustainably.